Prevalence of Musculoskeletal Disorders in Farmers of Ahmednagar District - R Murthy, Ms. Shruti; Nikhade, Dr. Nitin (International Journal of Innovative Research in Medical Science, 2017)
Background: Ahmednagar is an agro based district. The farmers have to adapt to the various uncertainties like environmental changes, physical stress, psychosocial problems, type of work, etc. Work-related musculoskeletal disorders (WMSDs) are a product of acute injuries from a one-time trauma or multiple traumas. There are several studies showing that farmers have a higher risk of developing MSDs than any other group of people. However, there are hardly any studies that focus on the country’s farming community, which constitutes more than 58 percent of the Indian work force. Therefore this study is being carried out to analyze the prevalence of musculoskeletal disorders in farmers. Aim: To find out the prevalence of musculoskeletal disorders in farmers of Ahmednagar district. Method: A study was conducted in Ahmednagar district on 100 farmers aged 30-60 years using the Nordic Musculoskeletal Questionnaire. The demographic data such as Age, Sex, Height, Weight, BMI etc. was taken for each subject and the subjects was interviewed regarding the, present and past history, occupational history, family history and surgical history if any. The data was collected by using Nordic Musculoskeletal Questionnaire in local language (Marathi).Data was recorded on assessment sheets. Results: The knee joints [25%], followed by the low back region [24%] were the commonest areas affected in the subjects. The neck region [14%] and shoulders [14%] were equally affected. The elbow [3%] and wrist [5%] were the least affected areas comparatively. Conclusion: From this study we can conclude that there is a high risk of developing musculoskeletal disorders in farmers especially in the knees and low back region.